2017
DOI: 10.3892/ol.2017.5960
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant fibromodulin and decorin effects on NF-κB and TGFβ1 in the 4T1 breast cancer cell line

Abstract: Abstract. Constitutive activation of nuclear factor-κB (NF-κB) stimulates cell proliferation and metastasis, and inhibits apoptosis in breast cancer. Transforming growth factor-β (TGF-β) signaling pathway is deregulated in breast cancer progression and metastasis. The aim of the present study was to investigate the inhibitory effects of the two small leucine rich proteoglycans fibromodulin (Fmod) and decorin (Dcn), overexpressed using adenovirus gene transfer, on NF-κB-activity and TGF-β1-expression in the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…We previously reported that serum decorin levels are positively correlated with skeletal muscle mass in patients with HCC [16]. Decorin is also reported to interact with transforming growth factor-β and receptors of tyrosine kinase such as epidermal and insulin-like growth factors [17], leading to suppression of proliferation of various tumor cell lines, including HCC cell lines [18][19][20]. In addition, decorin is known to be expressed in various tissues including intestinal tissue, cardiac tissue, and adipose tissue and is known to regulate autophagy, inflammation, and glucose homeostasis [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that serum decorin levels are positively correlated with skeletal muscle mass in patients with HCC [16]. Decorin is also reported to interact with transforming growth factor-β and receptors of tyrosine kinase such as epidermal and insulin-like growth factors [17], leading to suppression of proliferation of various tumor cell lines, including HCC cell lines [18][19][20]. In addition, decorin is known to be expressed in various tissues including intestinal tissue, cardiac tissue, and adipose tissue and is known to regulate autophagy, inflammation, and glucose homeostasis [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…It has been proven that TGF-β is involved in cell development, angiogenesis, immune response, and inflammation [28][29][30]; signaling disorders involving TGF-β lead to multiple pathological processes, including cancer [31]. Studies have shown that in the case of Fmod−/−, deficient migration can be relieved by adding exogenous TGF-β1, which indicates that the absence of Fmod alters the normal temporospatial pattern [32]. Zheng et al showed that Fmod interacts with TGF-β during cutaneous repair and scar formation; wound closure can be delayed in Fmod-deficient mice, which is accompanied by an increase of TGF-β3 signaling [7].…”
Section: Discussionmentioning
confidence: 99%
“…Fmod has been shown to successfully inhibit the nuclear factor-kB (NF-kB) signaling and induce fibroblast apoptosis (Lee and Schiemann, 2011). Dawoody Nejad et al, 2017 demonstrated that recombinant Fmod was able to suppress TGFb1 and NF-kB activity in vitro in a highly metastatic breast cancer cell line (Dawoody Nejad et al, 2017).…”
Section: Fibromodulinmentioning
confidence: 99%